Not Just More, but Better : Fostering Quality of Employment for Women - Datta, Namita; Kotikula, Aphichoke (World Bank, Washington, DC, 2017)
Despite progress on women’s labor force participation in the past few decades, there remain persistent gender gaps across multiple dimensions of job quality. Women generally earn less than men. Gaps are particularly acute in the Middle East and North Africa but also persist in high income Organization for Economic Co-operation and Development (OECD) countries. Women tend to be concentrated in less productive jobs, run enterprises in less productive sectors, and are more likely to do part-time and temporary jobs with fewer avenues for advancement, than men. Women are particularly concentrated into the more invisible activities, such as domestic labor and unpaid work or work in the informal sector in jobs that lack security and are not covered by labor laws. In other words, there are persistent gender gaps not only in labor force participation rates or the quantity of jobs, but perhaps more importantly, in the quality or types of jobs that men and women do. Having access to quality jobs which are stable, decent, secure, and productive is even more important from a gender perspective because women are more likely than men to be over represented in low paying, part time, informal, and low productivity jobs. This paper explores the multiple dimensions of women’s access to good quality jobs, factors contributing to gender gaps, and possible solutions or actions that have worked in different countries.